Pengembangan Media Pembelajaran Matematika menggunakan Google Site dengan Pendekatan Metakognisi untuk Kelas XI - Disca Amellya; Khasanah, Uswatun (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2021)
Online learning now days, learners experience a decrease in the understanding of learning materials. This happens, because the learning media used by teachers still uses conventional learning media such as Ms.word / PDF. Moreover, learners are required to learn independently. Therefore, a learning media is needed to help students overcome the problem. This research is a website-based learning media development research that aims to help students in the online learning process, as well as knowing the feasibility of learning media using google with a metacognition approach to problem solving. The data collection instruments used are observations and questionnaires. The development of this learning media, is done by the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. Technical data analysis is carried out qualitatively to measure data descriptively and quantitatively to calculate the score of the feasibility trial results of learning media that researchers have developed. The results of this learning media development research based on the feasibility of learning media earned a percentage on an 83% basis with excellent categories. For trials the metacognition capability of problem solving obtained a percentage of 76% with good categories. Thus, the learning media of mathematical learning media using google that researchers developed is very feasible to use.